Public administration as an interdisciplinary field: Assessing its relationship with the fields of law, management, and political science - Wright, Bradley E. (2011)
Public administration is an interdisciplinary field, building on a variety to disciplinary approaches and values. But how well does the field of public administration reflects those values and processes? In contrast to previous arguments regarding the degree to which the field does or should incorporate values and lessons from other academic disciplines, this study provides a systematic assessment of the field's reliance on research and theory from the fields of law, management, and political science. An analysis of journal citations across these fields suggests that research in public administration is largely isolated from the three disciplines that are commonly believed to form its foundations. - Reproduced.
Keywords: Public administration